2022
DOI: 10.3389/fevo.2022.817864
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Hematological Indices, Oxidative Stress, and Immune Function Among Male Song Sparrows From Rural and Low-Density Urban Habitats

Abstract: A central theme in the field of ecology is understanding how environmental variables influence a species’ distribution. In the last 20 years, there has been particular attention given to understanding adaptive physiological traits that allow some species to persist in urban environments. However, there is no clear consensus on how urbanization influences physiology, and it is unclear whether physiological differences in urban birds are directly linked to adverse outcomes or are representative of urban birds ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 85 publications
1
0
0
Order By: Relevance
“…Bauerová et al ( 2017 ) and Herrera-Dueñas et al ( 2014 ) both found that oxidative stress was detected in RBCs, in conjunction with lower Hb and packed cell volume (PCV) concentrations in birds that inhabited urban areas opposed to rural areas. This is consistent with Goodchild et al ( 2022 ) where Song Sparrows ( Melospiza melodia ) inhabiting suburban areas displayed lower Hb concentrations compared to individuals inhabiting rural areas. However, the study did not find any significant differences in any of the oxidative stress markers tested (GSH, d-ROMs, HOCI neutralisation) between sites, which could suggest Hb concentrations are not dictated directly by urbanisation.…”
Section: Discussionsupporting
confidence: 92%
“…Bauerová et al ( 2017 ) and Herrera-Dueñas et al ( 2014 ) both found that oxidative stress was detected in RBCs, in conjunction with lower Hb and packed cell volume (PCV) concentrations in birds that inhabited urban areas opposed to rural areas. This is consistent with Goodchild et al ( 2022 ) where Song Sparrows ( Melospiza melodia ) inhabiting suburban areas displayed lower Hb concentrations compared to individuals inhabiting rural areas. However, the study did not find any significant differences in any of the oxidative stress markers tested (GSH, d-ROMs, HOCI neutralisation) between sites, which could suggest Hb concentrations are not dictated directly by urbanisation.…”
Section: Discussionsupporting
confidence: 92%
“…Adult song sparrows in our urban and rural study sites show consistent behavioral differences (Hyman et al 2004, Evans et al 2010, Davies and Sewall 2016, Davies et al 2018, Fossett and Hyman 2021) and urban birds have higher reproductive success (Lane et al 2023). However, hormone concentrations, oxidative stress, and hematological measures do not reliably differ across habitats (Foltz et al 2015, Lane et al 2021, Goodchild et al 2022, nor is there detectable genetic differentiation between birds at our rural and urban sites (Brewer et al 2020). Song sparrows are a common host for brown-headed cowbirds (Hauber and Russo 2000), and at our study sites brood parasitism occurs at high rates in urban habitats but is very rare in rural habitats (Lane et al 2023).…”
Section: Introductionmentioning
confidence: 58%
“…These measures have the potential to reveal both pathological effects of living in urban habitats and provide insight into the adaptive mechanisms underpinning responses that facilitate urban living (Isaksson 2015). Previous work has shown associations between urbanization and altered levels of hormones, oxidative stress, hematological parameters, and immune function (Bonier 2012, Isaksson 2015, Isaksson 2018, Goodchild et al 2022, Bonier 2023. Additionally, there is increasing interest in the impacts of urbanization on telomeres -tandem repeats of DNA and a shelterin protein complex at the end of chromosomes (Shay andWright 2019, Salmón andBurraco 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This refutes both the idea that urban males are facing a trade-off between territorial defense and parental care, and that urban habitats compromise male parental care. Previously, researchers found that urban male songbirds in this population had better body condition and access to greater fat reserves compared to rural (Goodchild et al, 2022), suggesting that birds in urban habitats are of higher quality than their rural counterparts and are therefore released from constraints experienced by other birds (Reznick et al, 2000). Additionally, urban males likely have different time and energy budgets compared to rural.…”
Section: Discussionmentioning
confidence: 84%